Systematic approach to celiac disease: a comprehensive review for primary providers - Cortés Pedro; Harris Dana M; Bi Yan (Sciendo, 2022)
Celiac disease is an immune-mediated illness to gluten exposure in genetically susceptible patients. It is characterized by chronic lymphocytic inflammation of the small bowel leading to villous atrophy and its associated complications. The global prevalence of celiac disease is increasing, due in part to improved screening tests and simplified diagnostic criteria. Novel therapies are being developed and include proteolytic enzymes, sequestering agents, and immunotherapies. A strict gluten-free diet, however, remains the mainstay of treatment. In this comprehensive review, we discuss the epidemiology, definitions, diagnosis, and treatment of celiac disease.